Arcano 17, de André Breton : magia e transcendência - Ornelas, Fernanda Taís (2017)
The present study analyses, through an exam of the surrealist thought and its magic, esoteric and philosophic bias, the presence of magic, esotericism and transcendence in André Breton‟s Arcanum 17, wrote in 1944. To this regard, this study is based on the main ideas and evolution of the French movement throughout the years, exposed by authors such as Maurice Nadeau (2008), Marguerite Bonnet (1988), Jacqueline Chénieux-Gendron (1992) and Octavio Paz (2001) to examine the presence of the Hermeticism, Alchemy and Kabbalah, the three main influences of Surrealism regarding the esoteric tradition, highlighted by critics such as Octavio Paz (2001), Maria Lúcia Dal Farra (2008), Claudio Willer (2008) e Michel Carrouges (1950). However it is less influential, the importance of Georg Wilhelm Friedrich Hegel‟s absolute idealism will also be analyzed based on Anna Balakian‟s (1986) and Marguerite Bonnet‟s (1992) studies. Finally, this study also draws on the symbolic analysis of the elements of the text, grounded on Jean Chevalier‟s and Alain Gheerbrant‟s (2014) work.